Mindful-Based Cognitive Therapy (MBCT) dan Self-Awareness untuk Menurunkan Kecemasan Ibu Hamil Primipara - Deacy Anindya Putri; Elly Yuliandari Gunatirin (Journal An-Nafs: Kajian Penelitian Psikologi, 2020)
This study discusses the anxiety of primiparous pregnant women before delivery. Primiparous pregnant women are mothers who first have children, so anxiety often arises. Lack of Self-Awareness in primiparous pregnant women, especially those who experience anxiety has its impact. Self-awareness is the ability of a person to judge and place himself in certain conditions. This topic was taken because of the increasingly widespread anxiety in primiparous pregnant women, which resulted in less optimal pregnancy during the psychological impact. The method used in this study is a single case experiment. Giving Mindful-Based Cognitive Therapy (MBCT) is considered effective for reducing anxiety in primiparous pregnant women before delivery. The MBCT session that given relates to inner self-awareness, to increase the participant's self-awareness. Participants' anxiety was measured using the Pregnancy-Related Anxiety Scale (PRAS), while Self-Awareness would be measured using the Mindfulness Attention and Awareness Scale (MAAS). This study involved 2 participants who received intervention for 4 weeks. The results of the study were analyzed with trend analysis. As a result, both participants experienced decreased anxiety before delivery and increased self-awareness after getting MBCT intervention.